The effect of selenium on the immune status in the complex treatment of children with autoimmune thyroiditis - G. G. Gabulov (Rossijskij Vestnik Perinatologii i Pediatrii, 2019)
The authors studied the effect of selenium on the dynamics of immune system indicators in children with autoimmune thyroiditis. They examined 31 children (average age of 11.16 ± 0.59 years). Group I included 17 children who took selenium (100 μg per day for 6 months) along with the basic treatment. Group II (n=14) took L-thyroxin. The control group included 15 healthy children of the same age. The average level of selenium in children of Group I and II was 69.23 ± 1.52 μg / l at the beginning of the study, in the control group it was 114.8 ± 3.18 μg / l. Before treatment, children in Group I and II had T-cell suppression, the average level of all cytokines (especially TNF-α and IL-6) was significantly higher than in practically healthy children. The study demonstrated that the level of the thyroid tissue antibodies decreased significantly (p=0.001) with an increase in the level of selenium in the blood serum. By the end of the study the content of IgA (p=0.012) and IgG (p=0.044) in Group I, as well as the number of lymphocytes CD3 + (p=0.008), CD4 + (p=0.015), CD16 + / 56 + (p=0.010) significantly increased. The authors observed statistically significant decrease in the levels of TNF-α (p=0.028), IL-6 (p=0.002) and IL-1β (p=0.009) in children who took selenium in addition to the main treatment. Thus, the results of the study suggest that selenium in the complex therapy of autoimmune thyroiditis significantly reduces the titer of antithyroid antibodies and positively affects a number of important indicators of immune homeostasis in children.